ASEAN's initiatives for regional economic integration and the implications for maritime logistics reforms. Issue 3 (9th November 2015) - Cheong, Inkyo; Suthiwartnarueput, Kamonchanok
Abstract : Purpose: – The purpose of this paper is to estimate the economic impact of reducing logistics cost on the demand for port throughput in the context of Association of Southeast Asian Nations' (ASEAN) regional economic integration and to realize the potential economic gains of the maritime logistics reform in the region. Design/methodology/approach: – The main part of this paper is to formulate conversion coefficients for containerized cargo to estimate the impacts of logistics reform on the demand for port throughput. These conversion coefficients, then have been used into a dynamic computational general equilibrium model using Global Trade Analysis Project database to explore the impact of logistics cost. Findings: – The study demonstrates that logistics efficiency is a challenge for ASEAN economic integration, providing significant implications for maritime logistics reforms. Research limitations/implications: – This study assumes uniform improvements of 5 and 10 percent in the logistics sector for all countries due to lack of detailed data on the logistics sectors in ASEAN countries. Practical implications: – The findings of this study could help ASEAN policymakers for deeper understanding of efficient maritime logistics in realizing the economic gains from its regional economic integration initiatives. Originality/value: – Although there are many descriptive studies on the importance of logistics efficiency in improving international competitiveness in a country or a region, these are not supported by quantitative assessment in the case of ASEAN. This study addresses the dearth of empirical evidence based on real data on trade and maritime cargo flows. This study contributes to highlighting that ASEAN countries should reform their logistics policies and practices.